A life cycle analysis techno-economic assessment framework for evaluating future technology pathways – The residential air-conditioning example. (1st June 2021) - Li, Yanjie; Nian, Victor; Li, Hailong; Liu, Shengchun; Wang, Yabo
Highlights: Developed a pathway-level life cycle analysis and techno-economic assessment method. The method can lead to transparent results for evidence-based policy making. The method is demonstrated using air-conditioning in Southeast Asia as case study. Refrigerant replacement can be equally important as energy efficiency improvement. Identified plausible technology pathways for HFC phase-down in Southeast Asia. Abstract: Clarity on cost and environmental benefits of individual technologies evaluated in a systemic and systematic manner is necessary in communicating the results at the policy level so as to enable effective decisions. Yet, the highly complex nature of many energy modelling tools makes it difficult for non-specialists to interpret and make sense of their results. An integrated life cycle analysis and techno-economic assessment framework is proposed in this study, as a first step towards developing an alternative and potentially more intuitive energy systems modelling tool. The residential air-conditioning sector in the Southeast Asian context is used as an example to demonstrate the advantages of the modelling methodology in profiling future technology pathways. The use of best available R32 technology can lead to cumulative savings of 2195 million tonnes of greenhouse gas emissions in the region by 2050; while the best available R407C technology has an average cost of $40.85 per tonne of greenhouse gas abatement. In addition, our modelling tool is capable of profiling energy outlooks for emerging economies and will be further integrated with hourly energy analysis frameworks in the next steps of development.